2016
DOI: 10.3892/mco.2016.1088
|View full text |Cite
|
Sign up to set email alerts
|

High expression of ADAMTS5 is a potent marker for lymphatic invasion and lymph node metastasis in colorectal cancer

Abstract: Abstract. Members of the ADAMTS family contain propeptide, metalloproteinase and disintegrin domains and serve key roles for cancer cell proliferation, progression and metastasis. Although overexpression of ADAMTS5 has been reported in glioblastoma, and head and neck cancer, little has been demonstrated in colorectal cancer types. The present study aimed to clarify the significance of ADAMTS5 for clinicopathological factors and prognosis in colorectal cancer. The mRNA expression of ADAMTS5 was measured in 143 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…When lymphatic vessels are distributed in the submucosa, lymph node metastasis is likely to occur when the tumor invades the submucosa. When the tumor invades the deep intestinal wall, the lymph node metastasis rate will increase significantly[ 28 , 29 ]. In our study, the lymph node metastasis rate of this group of patients with T1-stage CRC was 8.41%, which is mostly consistent with previous reports[ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…When lymphatic vessels are distributed in the submucosa, lymph node metastasis is likely to occur when the tumor invades the submucosa. When the tumor invades the deep intestinal wall, the lymph node metastasis rate will increase significantly[ 28 , 29 ]. In our study, the lymph node metastasis rate of this group of patients with T1-stage CRC was 8.41%, which is mostly consistent with previous reports[ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of ADAMTS5 was increased in late CRC stages, and ADAMTS5 may have served as the fundamental component of tumor invasion through degrading ECM so as to promote tumor progression to more advanced stages of CRC[ 35 ]. The ratios of lymphatic invasion and lymph node metastasis were significantly higher in patients with CRC and high ADAMTS5 expression, but such expression did not affect OS and DFS[ 36 ]. However, Li et al [ 37 ] suggested that ADAMTS5 overexpression inhibited the invasion and migration of CRC, and ADAMTS5 was more hypermethylated in tumor tissue compared with normal tissue, corresponding to poor OS and DFS .…”
Section: Discussionmentioning
confidence: 99%
“…ADAMTS5 is overexpressed in CRC, promoting CRC metastasis and cancer cell invasion [ 37 ]. High expression of ADAMTS5 is a potent biomarker for lymphatic invasion and lymph node metastasis in CRC [ 38 ]. These results indicate that these molecules may be used as promising biomarkers and therapeutic targets for COAD.…”
Section: Discussionmentioning
confidence: 99%